Direct signals for large extra dimensions in the production of fermion pairs at linear colliders - Éboli, O. J P [UNESP]; Magro, M. B.; Mathews, P.; Mercadante, P. G. (American Physical Society (APS), 2001)
We analyze the potential of the next generation of e+e- linear colliders to search for large extra dimensions via the production of fermion pairs in association with Kaluza-Klein gravitons (G), i.e., e+e- →ff̃G. This process leads to a final state exhibiting a significant amount of missing energy in addition to acoplanar lepton or jet pairs. We study in detail this reaction using the full tree level contributions due to the graviton emission and the standard model backgrounds. After choosing the cuts to enhance the signal, we show that a linear collider with a center-of-mass energy of 500 GeV will be able to probe quantum gravity scales from 0.96 (0.86) up to 4.1 (3.3) TeV at a 2 (5)σ level, depending on the number of extra dimensions. ©2001 The American Physical Society.
Keywords: energy; gravity; mathematical analysis; model; molecular dynamics; physics; quantum mechanics; radiation dose; radiation energy; signal processing